Identification of Novel Imatinib-Resistant Genes in Gastrointestinal Stromal Tumors - Cao, Lei; Zheng, Kunming; Liu, Yanhong; Song, Peng; Wang, Chuntao; Wang, Hongzhi; Wang, Nan; Zhang, Shiwu; Zhao, Yongjie (Frontiers in Genetics, 2022)
Gastrointestinal stromal tumor (GIST) is considered a potentially malignant mesenchymal tumor of the gastrointestinal tract. Imatinib plays important role in the treatment of gastrointestinal stromal tumor.However, many people with GIST develop resistance to imatinib. The purpose of the present academic work was to identify significant genes with resistance to imatinib and their underlying mechanisms. A total of 897 differentially expressed gens(DEGs) were identified between the Imatinib sensitive cell line GIST882 and Imatinib resistant cell line GIST430. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses of the DEGs were performed using the “clusterProfiler” R package. The top ten up-regulated genes (NDN,FABP4,COL4A1,COLEC11,MEG3,EPHA3,EDN3,LMO3,RGS4,CRISP2) were selected for subsequent analysis.Between GIST882 and GIST430,the differential expression of EPHA,FABP4,COL4A1,RGS4 were verified by PCR. PPI network was Constructed to explore the genes that interact with the EPHA3